2020
DOI: 10.1186/s12920-020-00844-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor development and attention problems caused by a splicing variant of CNKSR2

Abstract: Background Mutations in CNKSR2 have been described in patients with neurodevelopmental disorders characterized by childhood epilepsy, language deficits, and attention problems. The encoded protein plays an important role in synaptic function. Case presentation Whole-exome sequencing was applied to detect pathogenic variants in a patient with clinical symptoms of psychomotor development, attention deficit, poor logical thinking ability, and an intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Of the 13 affected males in our cohort, ten represent de novo cases, while in three the variants are maternally inherited. Recent articles have indicated that females harboring heterozygous CNKSR2 pathogenic variants may have seizures, with some also manifesting neurodevelopmental concerns (family 26, [14]; family 27, [2]; mother and sister of family 19, [5]; mother of family 25, [6]; mother of family 26, [20]). However, for another six mothers (three mothers in this cohort, family 14, [1]; family 15, [7]; family 16, [17], there were no reported seizures or intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 13 affected males in our cohort, ten represent de novo cases, while in three the variants are maternally inherited. Recent articles have indicated that females harboring heterozygous CNKSR2 pathogenic variants may have seizures, with some also manifesting neurodevelopmental concerns (family 26, [14]; family 27, [2]; mother and sister of family 19, [5]; mother of family 25, [6]; mother of family 26, [20]). However, for another six mothers (three mothers in this cohort, family 14, [1]; family 15, [7]; family 16, [17], there were no reported seizures or intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial characterization of a boy affected with a pathogenic variant in CNKSR2 by Houge et al [7] (mental retardation, X-linked, Houge type (MRX-SHG), MIM 301008), there have been a total of 20 affected males described in the literature, all with a consistent clinical phenotype of intellectual disability, developmental delay, and epilepsy [1,2,5,6,15,17,20]. Early developmental progress may be normal in rare instances, but global delays are observed consistently after the onset of seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A). In addition, eight kinds of variants in CNKSR2 had been reported in the literature, [ 1 , 5 , 7 10 ] there are c.452insA(p.Asp152Argfs ∗ 8), c.2024_2027delAGAG (p.Glu675Glyfs ∗ 41), c.246–247delAG(p.Thr83Lysfs ∗ 30), c.457_461del(p. Tyr153Serfs ∗ 5), c.2314 C > T(p.Arg712 ∗ ), c.2185C > T(p.Arg729 ∗ ), c.2304G > A (p.Trp768 ∗ ) and c.1904+1G > A (Fig. 2 B).Among the twenty one cases reported, nine of them have their genotype being inherited from mothers(Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serious attention deficit and hyperactivity have frequently been observed [ 53 ]. Multiple types of variations, including deletion [ 8 , 54 , 55 , 56 , 57 ], frame shift [ 54 , 57 , 58 ], splicing [ 57 , 59 ], and nonsense variations [ 53 , 57 , 60 , 61 , 62 ] have been reported in patients suffering from MRXSHG ( Figure 2 and Table 1 ). Severely affected patients were all hemizygous males and heterozygous female carriers of variants that exhibited moderate to mild phenotype or unaffected ( Table 1 ), probably because of the production of CNKSR2 from the normal allele.…”
Section: Cnksr2 and Neurodevelopmental Disordersmentioning
confidence: 99%